(untitled) (TEST Trento Student Law Review, 2021)
This article addresses the problem of the exploitation of children in the Orinoco Mining Arc, a mining area located in the Bolivarian Republic of Venezuela. The article is prepared under a documentary research scheme – which is based on both legal texts and journalistic sources – and with a qualitative approach. In particular, this research explores whether it is possible to attribute responsibility for the occurrence of the events of the Orinoco Mining Arc to the Government of Venezuela, especially, taking into account the international commitments for the protection of human rights which Venezuela has undertaken. The analysis reveals that the government of Venezuela can be found guilty – both for its action and omission – for the violation of children’s rights in the Orinoco Mining Arc. Venezuela has indeed failed to guarantee the respect of fundamental human rights, such as the right to life and to physical and mental integrity, and this way it has violated it has contravened the obligations of international documents such as the Universal Declaration of Human Rights. For this reason, Venezuela must develop new public policies to tackle the serious violations of fundamental human rights and restore its national respect for fellowship among people.